Exploring flavone reactivity: A quantum mechanical study and TD-DFT benchmark on UV-vis spectroscopy - Bhatia, Manjeet (European Journal of Chemistry, 2025)
Flavones are known for their broad spectrum of pharmacological and biological activities, making them promising candidates for drug development and complementary medicine. In this study, a comprehensive analysis of the chemical reactivity, kinetic stability, and biological potential of the flavone molecule is performed using density functional theory (DFT) at the D3-B3LYP/6-311++G(d,p) level. The key molecular properties-proton affinity (PA), ionization energy (IE) and electron affinity (EA)-are calculated alongside global reactivity descriptors such as chemical potential (μ), chemical hardness (η), softness (σ), electrophilic index (ω), and electronegativity (χ). To ensure the reliability and cost-effectiveness of the chosen DFT method, a comparative analysis is performed using various functionals, including D3-B3LYP, wB97XD, M06-2X and MP2. Furthermore, time-dependent DFT (TD-DFT) calculations are performed with multiple functionals B3LYP, CAM-B3LYP, PBE0, M06-2X, LC-wHPBE and wB97XD to investigate the excited-state properties and UV-visible absorption spectra of flavone. The results indicate that CAM-B3LYP, M06-2X, and wB97XD provide the most accurate predictions for the absorption characteristics of the flavone molecule.